O efeito da sobrecarga de informação na atenção visual: o papel da indulgência e da temporalidade - Ruffatto, Juliane (Universidade do Vale do Rio dos Sinos, 2021)
Consumers often make decisions about outcomes and events that occur over time. Faced with an opportunity for indulgence, officials can consult their memoirs to see if there has been enough progress toward a goal of self-regulation to justify the indulgence. Thus, this thesis aims to analyze the influence of temporality and indulgence in the relationship between information overload and visual attention. To this end, two experimental studies were developed using eye tracking technology in different contexts of choice, in a laboratory environment, the first one simulating a restaurant menu with different food options, and the second, the food choice was made via mobile commerce , simulating a mobile app. In both studies, information overload (high and low) was manipulated by the number of attributes of choice options available to the subjects. Note that increasing information overload also increases visual attention, that is, visual attention is greater in an overloaded context; that indulgence partially moderates the relationship between information overload and visual attention, this effect being observed only in the context of low overload in both studies. Also, partial moderation of temporality was observed. The test results of this alternative results differ between the two experimental studies. In study 1, simulating the choice of a restaurant menu, a difference was observed explained at the end of the objective time, when the indulgence presents greater visual attention in the context of attention overload, compared to the context of low overload, when self-control is greater. attention levels of visual attention. In study 2, in a context of low overload, visual attention was greater for indulgent choices at the beginning of the objective time, whereas in high overload, visual attention was greater for self-control at the end of the objective time. Such results obtained that at the beginning of the journey of choice via cell phone, perhaps due to the summarized size of the screen and the order in which the options were presented, attention was focused on indulgent options. In the menu, the consumer could explore how options and ended up focusing the greatest visual attention on self-control choices. These results indicate that information overload and visual attention vary along with time flow in different ways. For example, companies operating via mobile commerce can focus their attention on the first product information. Low information overload can help consumers focus on self-control, stimulating the consumer's search effort through visual triggers that highlight healthier foods and contribute to obesity control policies. Based on the findings, this thesis contributes to the marketing literature on food choices in an environment with low information overload, greater visual attention to less indulgent foods, suggesting that this phenomenon will relate to the profile of the consumer, who makes their choices. with greater caution and attention, taking into account self-control to choose your food, and the use of eye tracking technology to investigate a phenomenon of consumer choices for marketing research.
Keywords: Sobrecarga de informação; Atenção visual; Indulgência; Temporalidade; Information overload; Visual attention; Indulgence; Temporality; ACCNPQ::Ciências Sociais Aplicadas::Administração